The teller of small fortunes - Leong, Julie (Ace, 2024)
"A fortune teller finds an unexpected family on her journeys in this heartwarming and charming fantasy debut. Tao, an immigrant fortune teller, lives in a wagon and roams the dusty outskirts of the kingdom of Eshtera. Fleeing a troubled past, she travels between villages telling only small fortunes: whether it will hail next Thursday; what boy will kiss which barmaid; when the cow will calve. Big fortunes come with big consequences...which she wants to avoid at all costs. Life on the road can be lonely but, to Tao's surprise, companionship comes unexpectedly. She encounters Mash and Silt, an ex-mercenary and semi-reformed thief; the oddball pair endear themselves to Tao and enlist her in the search for Mash's lost daughter. Next the trio finds Kina, a brilliant baker, with a knead for adventure. And, finally, Fidelitus rounds out their party, a cat smart enough to mark the travelers as ready suppliers of fish. As they journey together across Eshtera, confronting small-minded villagers and philosophizing trolls alike, Tao's unlikely new friends break down her walls and unravel her secrets. Ultimately, Tao must decide what's more important: her hard-won freedom, or reuniting a family not her own"--